INTEGRASI TRI HITA KARANA UNTUK MENINGKATKAN MINDFULNESS BERKOMUNIKASI SISWA - I Nyoman Adi Susrawan,; Rita Widiya Sari,; Dewa Gede Bambang Erawan, (Journal of Innovation Research and Knowledge, 2025)
This study focuses on enhancing mindfulness in communication among Grade X TAV-1 students at SMK Negeri 1 Denpasar through the integration of Tri Hita Karana values. The study employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, which includes four stages in each cycle: planning, action, observation, and reflection.. The findings clearly showed a significant improvement after implementing Tri Hita Karana values in learning to foster mindfulness in communication. This is evidenced by the continuous increase in students’ test scores: the average pre-test score was 65.5, which increased to 82.4 in the first cycle and further to 91.4 in the second cycle. Therefore, this research is expected to contribute to the development of more mindful communication skills based on local wisdom